Structural characterization, biofunctionality, and in vitro digestibility of exopolysaccharides from Lactiplantibacillus plantarum E1K2R2 - Aliouche, Nadia; Sifour, Mohamed; Tornaci, Selay; Toksoy Oner, Ebru; Dertli, Enes; Ouled-Haddar, Houria (SPRINGERNATURE, 2025)
Recently, microbial polysaccharides have gained significant importance as biomaterials, owing to their health benefits and inherent biocompatibility. Accordingly, the present study focuses on characterizing exopolysaccharides (EPS) from Lactiplantibacillus plantarum E1K2R2, investigating their structure, biocompatibility, antioxidant properties, antitumor effects, and digestibility under simulated saliva and gastrointestinal conditions. The EPS was identified as a heteropolysaccharide primarily composed of galactose and glucose monomers, with a molecular weight ranging from 3.15 x 103 to 3.95 x 105 Da. The measured particle size was 498.7 nm, while its negative zeta potential (- 7.20 mV) pointed to an acidic profile. FTIR analysis further supported this finding by identifying characteristic hydroxyl and carboxyl functional groups at 3273.57 cm-1 and 1646.91 cm-1, respectively. 1H NMR spectroscopy demonstrated that monomers in the EPS were linked by alpha- glycosidic bonds. Functionally, the EPS displayed dose-dependent antioxidant activity within 0.1-1 mg/mL, equivalent to 0.07-0.17 mM/mL ascorbic acid, with ABTS+ radical scavenging ranging from 33.63 to 65.63%, demonstrating strong free radical-scavenging potential. In cytotoxicity assays, the EPS moderately inhibited HepG2 cell proliferation (6.49-20.53%) while maintaining 95% viability in normal HUVEC cells at 1 mg/mL after 24 h of incubation, indicating selective cytotoxicity toward cancer cells and good biocompatibility with normal cells. The EPS also resists simulated saliva and gastrointestinal conditions and promotes the growth of some potential probiotic lactic acid bacteria, indicating that digestive conditions do not adversely affect the EPS. These findings suggest that EPS has promising applications due to its antioxidant, antitumor, and prebiotic contexts, supported by its high biocompatibility.
Keywords: Antioxidant activity; Anti-tumor activity; Biocompatibility; Exopolysaccharides; Structural characterization; ALPHA-D-GLUCAN; INHIBITORY-ACTIVITY; IDENTIFICATION; BIOACTIVITIES; STRAINS; AMYLASE; FOOD; Biotechnology & Applied Microbiology